Development Of Nanocasted Tin Oxide For Ethanol And Acetone Gas Sensor - Juhari, Jusliha (2018)
The understanding of sensing behaviour of most portable gas sensors available in the market is still limited. This research study aimed at the development of nanocasted mesoporous tin oxide (SnO2) for ethanol and acetone gas sensors. To achieve this goal, ordered mesoporous SnO2 materials were prepared by means of a nanocasting method using pre-synthesized ordered mesoporous silica (OMS) as hard templates. Effects of nanocasting parameters on the formation, structural and textural properties of ordered mesoporous SnO2, as well the ability to detect ethanol vapour were studied by employing the one-factor-at-a-time method. The thermal stability of ordered mesoporous SnO2 was also investigated for different calcination temperatures. The fabricated sensors in the form of thick-film configuration of ordered mesoporous SnO2 were further tested for ethanol vapour detection at operating temperatures between 150 °C and 400 °C. The sensing performance of the fabricated sensors was maximized under various operating parameters. It was found that all nanocasted mesoporous SnO2 materials exhibited well-defined, ordered mesostructured, and large specific surface area as well as high crystalline frameworks, indicating successful replication from the OMS templates. The best sensor produced was S(K80)- VASEM(2) with maximum sensitivity of ~28.15 towards 1000 ppm ethanol at an operating temperature of 300 °C. The sensitivity of S(K80)-VASEM(2) sensor was further enhanced by loading 5.0 weight% of basic oxide (La2O3) into SnO2 through direct synthesis that gave the highest sensitivity of ~52.57. The basic oxide could help the formation of ordered and stable mesoporous networks, high crystalline frameworks, large surface areas and the presence of basic sites. These factors increased the interaction between the ethanol molecules and the surface active sites of the SnO2 sensor. It also increased the selectivity in ethanol oxidation reaction that increased the dehydrogenation process. The 5.0LS(K80)-V(2)-DS sensor exhibited a moderate response time of 52 s and a short recovery time of 43 s as well as good selectivity to ethanol over acetone vapour. This sensor also demonstrated high stability, repeatability and reliable sensitivity after continuous use for 14 days. All the results showed that the nanocasting method is an effective and a simple way to prepare ordered mesoporous SnO2 materials with unique and enhanced structural and textural properties. The produced sensors also displayed excellent gas sensing performances in detecting ethanol vapour.